Underrated enemy – from nonalcoholic fatty liver disease to cancers of the gastrointestinal tract - Derra, Aleksandra; Bator, Martyna; Menżyk, Tomasz; Kukla, Michał (Clinical and Experimental Hepatology, 2018)
Nonalcoholic fatty liver disease (NAFLD) is intrahepatic ectopic lipid deposition which is present despite a lack of other causes of secondary hepatic fat accumulation. It is the most common chronic liver disorder in the welldeveloped countries. NAFLD is a multidisciplinary disease that affects various systems and organs and is inextricably linked to simple obesity, metabolic syndrome, insulin resistance and overt diabetes mellitus type 2. The positive energy balance related to obesity leads to a variety of systemic changes including modified levels of insulin, insulin- like growth factor-1, adipokines, hepatokines and cytokines. It is strongly linked to carcinogenesis and new evidence proves that NAFLD is associated with higher risk of all-cause mortality and cancer-specific mortality among cancer survivors. This article focuses on the association between NAFLD and extrahepatic gastrointestinal tract cancers, aiming to shed light on the pathomechanism of changes leading to the development of tumors.